2013
DOI: 10.1016/j.worlddev.2012.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Soybeans, Poverty and Inequality in the Brazilian Amazon

Abstract: Abstract:The recent growth of soybean cultivation in the Brazilian Amazon has been unprecedented, even as the debate continues over its economic and environmental consequences. Based on contemporary datasets as well as our own field studies, this paper examines the social and economic costs and benefits of increases in soybean production for local populations. After presenting some background information on the rise of soybean cultivation in Brazil we examine the relationship between increases in soybean produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 8 publications
5
51
0
4
Order By: Relevance
“…The main question addressed by this investigation is if agricultural expansion brings socioeconomic development, meaning not only growth in the Gross Domestic Product (GDP), but also better income, health and education (HDI) to municipalities where it takes place [8]. This question relates to the general perception that, by supporting commodity crops such as soy, local inequality and poverty are accentuated, since such crops require large areas and less labor per hectare [35,36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main question addressed by this investigation is if agricultural expansion brings socioeconomic development, meaning not only growth in the Gross Domestic Product (GDP), but also better income, health and education (HDI) to municipalities where it takes place [8]. This question relates to the general perception that, by supporting commodity crops such as soy, local inequality and poverty are accentuated, since such crops require large areas and less labor per hectare [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, agriculture intensification in the State of Mato Grosso, with soy and double-cropping (e.g., soy followed by maize or cotton) has been a true engine of lasting socioeconomic development [6,7]. Weinhold et al [8] and Tristich and Arvor [9] broaden this type of analysis from the state level to the Brazilian Amazon region, concluding that socioeconomic indicators have improved with agriculture intensification, without a direct relationship with deforestation, refuting the hypothesis of boom-and-bust development. Garret and Rausch [4] included all municipalities of Brazil in their analysis, grouping them according to prevalent land cover: soy, sugarcane, cattle and nonagricultural municipalities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, these ecosystems are critically threatened by agricultural expansion for internationally traded commodities such as soybeans, palm oil, and beef (Hansen et al 2013). As this multibillion dollar segment of the global economy has grown it has been accompanied by an increasing concentration of the tropical land base into fewer large farms (Pacheco 2012a, VanWey et al 2013, Weinhold et al 2013). Yet, a majority of the farmers in humid forests remain impoverished, often depending on subsistence agriculture for their livelihoods (Sunderlin et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The world soybean production increased by 4.6% annually from 1961 to 2007 and reached average annual production of 217.6million tons in 2005-2007(Masuda & Goldsmith, 2014. Weinhold and Killick (2011) reported that, the increase of soy production both reduces poverty indicators and raises median rural incomes. Soybean cultivation is highly concentrated geographically, with only four countries-USA, Brazil, Argentine and China-accounting for almost 90% of wold output.…”
Section: Introductionmentioning
confidence: 99%